Telescoping error in recalled food consumption: Evidence from a survey experiment in Ethiopia - Abate, Gashaw T.; de Brauw, Alan; Gibson, John P.; Hirvonen, Kalle; Wolle, Abdulazize (Oxford University Press, 2022)
Telescoping errors occur if survey respondents misdate events from outside the reference period and include them in their recall. Concern about telescoping influenced the design of early Living Standards Measurement Study (LSMS) surveys, which used a two-visit interview format to bound food consumption recall. This design fell out of favor although not for evidence-based reasons. To measure the extent of telescoping bias on food consumption measures, a survey experiment was conducted in Addis Ababa, Ethiopia, randomly assigning households to either a two-visit bounded recall or a single visit unbounded recall. The average value of reported food consumption is 16 percent higher (95 percent CI: 7.4–25.9) in the unbounded single visit recall relative to the two-visit bounded recall. Most of the error is explained by difference in reported spending on less frequently consumed, protein-rich foods, so apparent food security indicators based on household diet diversity are likely overstated with unbounded recall.